Estimated ages of sediment core SF-07 obtained along the coastal plain of Babitonga Bay-Santa Catarina-Brazil - Cohen, Marcelo Cancela Lisboa; Fontes, Neuza; Rodrigues, Érika do Socorro Ferreira; Pessenda, Luiz C R; França, Marlon; Garret, Ed; Ryu, Junghyung (In: Cohen, MCL et al. (2025): Topographic, vegetation, radiocarbon and stratigraphic data from Babitonga Bay-Santa Catarina-Brazil [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.985002, 2025)
The cores were collected during the winter season in August 2017 using Russian-type sampling equipment. Sediment cores were obtained from tidal flats colonized by mangroves (SF-07, SF-08), herbs (SF-09), and ombrophilous forest (SF-10).
Keywords: isotopes; mangrove; radiocarbon age; South Brazil